Characterization of HTRB stress effects on SiC MOSFETs using photon emission spectral signatures. (September 2017) - Moultif, N.; Joubert, E.; Masmoudi, M.; Latry, O.
Abstract: This paper presents a reliability study of a 1.2 kV SiC MOSFET under HTRB (High Temperature Reverse Bias stress by the photon emission (PE) and the spectral photon emission (SPE) techniques. The electrical characteristics analysis suggests failures related to the PN junction degradation. This hypothesis is confirmed by the PE and SPE techniques. Highlights: This paper presents a failure analysis study on a HTRB stressed SiC MOSFET, using PE and SPE techniques. Following the HTRB stress, degradation has been noticed on Idss, Vth, Cds, Cgs capacitance in the N-well side, and Rds on . The electrical parameters degradation suggests a degradation of the PN junction that could cause a charge (e-) migration. The hypotheses concluded from the electrical characterizations are proved by PE and SPE analysis.